Assessing the Impact of Institutional Renaming Policies on State Asset Administration: Evidence from the Directorate General of Higher Education, Indonesia - Harri Irawan; Agus Sjafari; Ipah Ema Jumiati (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
Institutional nomenclature changes within government ministries are part of broader bureaucratic reforms aimed at improving organizational effectiveness and policy coordination. However, such structural adjustments often generate administrative consequences at the operational level. This study aims to evaluate the impact of institutional renaming policies on the administration of State-Owned Assets (Barang Milik Negara/BMN) at the Secretariat of the Directorate General of Higher Education, Ministry of Higher Education, Science, and Technology, Indonesia. The study focuses on asset recording and the legal status of asset utilization following the institutional transition.This research employs a qualitative case study approach, with data collected through in-depth interviews, observation, and document analysis during the transition period. Data were analyzed using a descriptive-analytical approach based on the policy evaluation framework of Charles O. Jones, emphasizing policy substance, implementation, and outcomes.The findings indicate that nomenclature changes have had significant administrative impacts, including delays in asset recording, postponement of asset disposal processes, reduced data accuracy, and legal uncertainty regarding asset utilization. These issues are exacerbated by rigid bureaucratic procedures, limited inter-unit coordination, and insufficient human resource capacity. Consequently, a gap emerges between administrative records and the actual physical condition of assets, potentially affecting the accountability of public financial reporting.